Syaikh Ahmad Khatib Minangkabau dan Kontekstualisasi Syair Arab dalam Isbāt Al-Zain li Sulh Al-Jamā’atain - Ilyas, Ahmad Fauzi (Universitas Muhammadiyah Gorontalo, 2024)
This article focuses on the authority of Shaikh Ahmad bin Abdul Lati>f al-Khati>b al-Jawi> al-Minkabawi> or Shaikh Ahmad Khatib Minangkabau (1860-1916) - abbreviated as Shaikh Ahmad Khatib - in the field of Arabic poetry in his work, Isba>t al-Zain li Sulh al-Jama'atain bi Jawa>z Ta'addud al-Jumu'atain between pages 21-71. This work, although it discusses fiqh and his debate with Sayyid Usman Betawi over Friday prayers in Palembang at the end of the 19th century, contains many verses used in the context of making his argument. In fact, so far, he is only known as a figure in the fields of fiqh, tawhid, and tasawwuf. In this article, the side that has never been studied is from the side of his authority in Arabic poetry and then contextualizing the poetry in an argumentative debate with Sayyid Usman. Through a historical approach and Arabic literature, the results show that Syaikh Ahmad Khatib is an authoritative scholar in this field. This is because he is able to use it in the context of argumentation. However, his authority in this field is in the stage of quoting Arabic poetry from the compiler; not yet in the stage of creating. This article recommends that further research be conducted on Shaykh Ahmad Khatib's authority in this field in terms of his ability to create poetry in accordance with the rules and knowledge of Arabic literature.